An Immersive Investment Game to Study Human-Robot Trust - Zörner, Sebastian; Arts, Emy; Vasiljevic, Brenda; Srivastava, Ankit; Schmalzl, Florian; Mir, Glareh; Bhatia, Kavish; Strahl, Erik; Peters, Annika; Alpay, Tayfun; Wermter, Stefan (Frontiers in Robotics and AI, 2021)
As robots become more advanced and capable, developing trust is an important factor of human-robot interaction and cooperation. However, as multiple environmental and social factors can influence trust, it is important to develop more elaborate scenarios and methods to measure human-robot trust. A widely used measurement of trust in social science is the investment game. In this study, we propose a scaled-up, immersive, science fiction Human-Robot Interaction (HRI) scenario for intrinsic motivation on human-robot collaboration, built upon the investment game and aimed at adapting the investment game for human-robot trust. For this purpose, we utilise two Neuro-Inspired COmpanion (NICO) - robots and a projected scenery. We investigate the applicability of our space mission experiment design to measure trust and the impact of non-verbal communication. We observe a correlation of 0.43 (p = 0.02) between self-assessed trust and trust measured from the game, and a positive impact of non-verbal communication on trust (p = 0.0008) and robot perception for anthropomorphism (p = 0.007) and animacy (p = 0.00002). We conclude that our scenario is an appropriate method to measure trust in human-robot interaction and also to study how non-verbal communication influences a human’s trust in robots.